Comparing Study on Metal Rubber and High Polymer Rubber. (September 2020) - Lu, Chunhong; Bai, Yuwei; Zhang, Yuzhi; Tian, Guang
Abstract: In this paper, the metal rubber and rubber were systematically compared, on the basis of comprehensive comparison of the manufacturing technique property of the metal rubber and high polymer rubber, the physical and mechanical properties of the two materials, especially the elastic and damping properties, were emphasisly compared. Finally, the scope of application of the two materials was discussed. The results of this study has certain guiding significance for application of metal rubber properly by the researchers engaged in the vibration isolation and damping of engineering.